Analysis of Physics Education Students’ Computational Readiness in Modern Digital-Based Computational Learning - Muhammad Taufik; Wahyudi Wahyudi; Fathurrahman Fathurrahman (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to provide a more in-depth description of Physics Education students' computational readiness for modern computational learning utilizing digital technology. Twenty-eight students participated as respondents, and data were collected through five main indicators: digital literacy, computational mathematics skills, programming experience, device readiness, and the level of difficulty in understanding computational concepts. The results indicate that student readiness is still in the moderate category, especially in digital literacy and mathematics skills. The majority of students also lack adequate programming experience, requiring more intensive guidance when dealing with program syntax and logic. The devices used by students vary in performance, which also affects the smoothness of computational practice. Furthermore, the level of difficulty of computational concepts is quite high, especially in reading pseudocode and debugging. Overall, the findings of this study demonstrate the need for a more adaptive, gradual learning strategy that takes into account the diversity of student abilities.